Blood-Oxygenation-Level-Dependent-(BOLD-) Based R2′ MRI Study in Monkey Model of Reversible Middle Cerebral Artery Occlusion. (6th February 2011) - Zhang, Jing; Chen, Ying-min; Zhang, Yun-ting
Abstract : Objective . To investigate the value of BOLD-based reversible transverse relaxation rate (R2 ′ ) MRI in detecting ischemic penumbra (IP) in a monkey model of reversible middle cerebral artery occlusion (MCAO) and time evolution of relative R2 ′ (rR2 ′ ) in infarcted core, IP, and oligemia. Materials and Methods . 6 monkeys were used to make MCAO by the microcatheter method. MR scans were performed at 0 h (1 h after MCAO), 1 h, 3 h, 6 h, 12 h, 24 h, and 48 h after reperfusion. R2 ′ was calculated using quantitative T2 and T2 ∗ maps. Ischemic area was subdivided into infracted core, IP and oligemia. rR2 ′ was calculated respectively. Results . Reversible MCAO model for 4/6 monkeys was made successfully. rR2 ′ values were significantly different at each time point, being highest in oligemia followed by IP and infarcted core (P < .05 ). With reperfusion time evolution, rR2 ′ in infarcted core showed a decreased trend: sharply decreased within 6 hours and maintained at 0 during 6–48 hours (P < .05 ). rR2 ′ values in IP and oligemia showed similar increased trend: sharply increased within 6 hours, maintained a plateau during 6–24 hours, and slightly increased until 48 hours. Conclusion . BOLD-based R2 ′ MRI can be used to describe changes of cerebral oxygen extract in acute ischemic stroke, and it can provide additional information in detecting IP. The time evolution rR2 ′ in infarcted core, IP, and oligemia is in accordance with the underlying pathophysiology.